In a Spirit of Curiosity, Concern, Collaboration, and Humility: Considering the Work of Middle Grades Education in the Context of a Pandemic - Kristie W Smith; Kristina N Falbe (Middle Grades Review, 2020)
When we envision the ideals of middle school, we so often think about the importance of physical setting. Physical setting helps to create a material space for so many of the tenets of the middle school mindset. For example, “a successful (middle) school for young adolescents is an inviting, supportive, and safe place—a joyful community that promotes in-depth learning and enhances students’ physical and emotional well-being. In a school (with a material, physical setting), human relationships are paramount.” (National Middle School Association, 2010, p. 33). With the outbreak of Covid-19 and pandemic conditions forcing so many to shelter-in-place, our collective thinking about this ideal has been forced to shapeshift. Without prerequisite planning, the physical setting has become a digital setting. What are the challenges of such a sudden and unexpected shift? What are the trending topics scrolling our personal and professional timelines? What are the solutions? This is the developing story, told in two voices, of middle grades educators reflecting on, living through, and teaching within the current reality of pandemic conditions that have shifted our personal and professional paradigms. In this essay, we will share some of our challenges and in-progress solutions. We consider shifts in our practices and professional mindsets as we seek to thrive and to serve middle grades educators and students in two different contexts. We pose questions that have incomplete answers and share our imperfect thinking as we seek answers. Our mindsets are evolving even as we write. We consider this topic in a spirit of curiosity, concern, collaboration, and humility.
Keywords: Middle Grades Education; Pandemic; Middle Level Educators; Middle Level Teacher Educators